EFFICACY OF CHEMICAL PREPARATIONS IN THE CONTROL OF THE LESSER MULBERRY MOTH - Nosirova Z. G.; Aitbaeva M. D. (Galaxy International Interdisciplinary Research Journal, 2023)
Analysis of experiences on testing chemical preparations as “Binsegard”, “Alphamiline”, “Remon Star” in protection of mulberry nurseries from the dangerous pest mulberry pyralid has been presented. It has been shown that double processing these insecticides in summer period with an interval 30-35 days allows us in duration 15 days destroy pests up to 100% and up to the processed season end there are no signs of damage to the leaves of mulberry nurseries.